Sistem Pendukung Keputusan Untuk Menentukan Kelayakan Penerima Beasiswa Yayasan Dengan Metode AHP - Dewi Yohana br Ginting; Nirwan Sinuhaji (Bulletin of Computer Science Research, 2023)
STIT AL-Washliyah Binjai is one of the Technical Implementation Units of the Education Office located in Binjai. Scholarships must be awarded to deserving recipients and deserve to receive them. The selection process for those who are entitled to receive scholarships still experiences problems in the decision-making process. Because of the large number of students and the criteria determined to provide scholarship recipient decisions that are as expected. A decision support system using the Analytic Hierarchy Process (AHP) method provides convenience in assessing multiple criteria with a comprehensive framework for considering a hierarchical process. The purpose of this research is to design and create a decision support system (SPK) for the selection of scholarships and so that scholarships can be given appropriately to students who deserve to receive them. With the existence of research on the eligibility of scholarship recipients, it can make it easier for parties involved in determining who is entitled to get the scholarship, because in it various comparison stages have been carried out so as to produce results to determine students to get scholarships.